Fed-batch Cultivation of Pseudomonas Aeruginosa USM-AR2 Producing Rhamnolipid in Bioreactor through Pulse Feeding Strategy - Md Noh, Nur Asshifa; Mohd Salleh, Salwa; Abdullah, Amirul Al-Ashraf; Mohd Yahya, Ahmad Ramli (IACSIT Press, Singapore, 2012)
Pseudomonas aeruginosa USM-AR2 culture was proven to produce a glycolipid type biosurfactant, rhamnolipid. Fed-batch cultivation of P. aeruginosa USM-AR2 with different feeding strategies was carried out in bioreactor to increase the rhamnolipid production and productivity. The quantification of cell biomass, rhamnolipid produced and rhamnolipid activity were determined using absorbance measurement, orcinol assay and surface tension measurement. Batch cultivation in bioreactor gave a biomass of 9.4 g L-1 and rhamnolipid of 2.35 g L-1 in 72 hours. Fed-batch cultivation with pulse feeding strategy using diesel as carbon substrate was carried out at different feeding time interval. The best feeding mode was recorded to be 12 h-feeding interval which resulted in 12.6 g L-1 of biomass and 3.13 g L-1 of rhamnolipid achieved in shorter time, 48 hours cultivation. Higher productivity was achieved by gradually feeding the carbon source while maintaining the optimal culture conditions, which was 0.065 g L-1 h-1 compared to batch culture, 0.033 g L-1 h-1.The highest biomass and rhamnolipid production, 24.1 g L-1 and 13.4 g L-1, respectively was obtained when multiple substrates were fed (diesel and yeast extract). However the productivity was lower, 0.054 g L-1 h-1 due to the extension of working time.